2012
DOI: 10.1158/0008-5472.can-12-0324
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Homologous Recombination–Deficient Epithelial Ovarian Cancers: Sensitivity to PARP Inhibitors, Platinum, and Survival

Abstract: Up to 50% of epithelial ovarian cancers (EOC) display defects in the homologous recombination (HR) pathway. We sought to determine the ramifications of the homologous recombination-deficient (HRD) status on the clinicopathologic features, chemotherapy response, and survival outcomes of patients with EOCs. HR status was determined in primary cultures from ascitic fluid in 50 chemotherapy-na€ ve patients by a functional RAD51 immunofluorescence assay and correlated with in vitro sensitivity to the PARP inhibitor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 43 publications
(44 reference statements)
2
100
0
Order By: Relevance
“…Ideally, genome wide association studies and pharmocogenetic studies may elucidate variants of germline genetic variations in each individual that are linked to platinum agents' toxicities and their clinical efficacy. Indeed, there has been some progress in this area, with emerging evidence confirming that analysis of ERCC1 expression, BRCA mutations and homologous recombination defects maybe useful both prognostically and in predicting response to platinum based regimes [13,14,16,21,96] However, the exploration of alternate biomarkers to predict platinum response is currently in nascent stages. In vitro studies have shown potential links between SULF2 methylation and high cofilin-1 level with cisplatin resistance and steroid receptor co-activator 3 (SRC3) expression with general platinum resistance in ovarian cancer [97][98][99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, genome wide association studies and pharmocogenetic studies may elucidate variants of germline genetic variations in each individual that are linked to platinum agents' toxicities and their clinical efficacy. Indeed, there has been some progress in this area, with emerging evidence confirming that analysis of ERCC1 expression, BRCA mutations and homologous recombination defects maybe useful both prognostically and in predicting response to platinum based regimes [13,14,16,21,96] However, the exploration of alternate biomarkers to predict platinum response is currently in nascent stages. In vitro studies have shown potential links between SULF2 methylation and high cofilin-1 level with cisplatin resistance and steroid receptor co-activator 3 (SRC3) expression with general platinum resistance in ovarian cancer [97][98][99].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relationship between other mediators of DNA repair such as BRCA and response to platinum agents seemingly appears more consistent; whereby upregulation of BRCA1 (which mediates double strand break repair via homologous recombination) also induces platinum resistance [19] and conversely, BRCA mutations are a hallmark of platinum sensitivity [20]. The latter aspect is clearly exemplified by epithelial ovarian cancer in which at least 50% of cases harbour homologous recombination defects [21] which underpin the inherent platinum sensitivity of this disease at initial presentation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ovarian carcinomas with genomic HRD are known to be more sensitive to standard-of-care platinum therapy and to display better overall survival of the patients compared with non-HRD tumors (14,37). Although in small number, CDK12-inactivated tumors did not show any tendency to better overall survival compared with ovarian cancers without genomic HRD (P > 0.3, log-rank test; Fig.…”
Section: Cdk12 Td-plus Phenotype and Genomic Hrd Hallmarksmentioning
confidence: 93%
“…HR-deficient cells carry the genomic footprints of progressive accumulation of structural genomic aberrations, including regions of CNA and LOH. Tumors exhibiting subclonal CNA and LOH events are likely to have acquired HR defects and would be good candidates for treatment with platinum-based drugs or PARP inhibitors (Mukhopadhyay et al 2012;Wang et al 2012). Large-scale whole-genome sequencing studies of epithelial cancers coupled with reliable homologous recombination deficiency assays will be an appropriate way to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%